375 Vorinostat for Missense Mutated Von Hippel Lindau Disease Associated Hemangioblastomas: A Pilot Study. (April 2023) - Chittiboina, Prashant; Mandal, Debjani; Bugarini, Alejandro; Mastorakos, Panagiotis; Stoica, Stefan; Boyle, Jacqueline; Alvarez, Reinier; Edwards, Nancy A.; Scott, Gretchen; Smith, Carolyn; Maric, Dragan; Zhuang, Zhengping; et al.
Abstract : INTRODUCTION: Missense mutated VHL protein (pVHL) maintains intrinsic function but undergoes proteasomal degradation, loss of function and tumor initiation/progression of VHL-associated tumors. Histone deacetylase inhibitors (HDACi) can rescue missense mutated pVHL and arrest tumor growth in pre-clinical models. METHODS: Seven subjects with missense VHL received 400mg/day of vorinostat (7-days) and surgical resection of hemangioblastomas. We analyzed vorinostat-treated HBs (and paired untreated HBs from the same patients) for gene and protein expression in the pVHL-HIF-VEGF pathway, and protein-protein interactions. We explored the transcriptional landscape of these tumors with single nucleus gene expression analysis. We recapitulated patient specific missense mutations and validated the clinical findings using lentiviral expression recombinant constructs in VHL-/- 786-O cells. RESULTS: Short-term oral vorinostat was well tolerated by all patients (age 46.0 ± 14.5 years; 25-61 years). In the 6 evaluable tumors, pVHL expression in neoplastic stromal cells of vorinostat treated tumors was significantly elevated compared to untreated tumors (p = 0.01). We found transcriptional suppression of downstream effectors including VEGF-A and GLUT1 in human tumor samples and validated the effects in patient-specific missense mutations expressed in VHL 786-O cells. Mechanistically, we found that vorinostat prevented Hsp90 recruitment to missense mutated pVHL. The vorinostat effects on pVHL rescue, transcriptional repression and Hsp90-pVHL interaction was independent of the location of the mutation on VHL. Lastly, we found a HB stromal cell specific effect in suppression of pro-tumorigenic pathways with single nucleus gene expression analysis. CONCLUSIONS: Short-term treatment with vorinostat increased pVHL levels and suppressed tumor progression signaling in VHL-associated hemangioblastomas. These results indicate that proteostasis modulation can rescue tumor pVHL in germline missense mutated VHL patients and such treatment could arrest tumor growth.